Assessing Digital Divides in Higher Education During the Covid-19 Pandemic: Exploring an Evaluating E-learning System Success Model - Brett Payton; Laura Gomez Aurioles (International Telecommunications Society (ITS), 2021)
The global transition to online classes in higher education during the COVID-19 pandemic gave researchers the opportunity to evaluate eLearning in ways never before possible. This study extends a model for Evaluating eLearning System Success (EESS) and uses an information systems approach to explore the issue of digital divides within higher education during the global push to online learning. Preliminary findings suggest that instructor quality, learner quality, socioemotional support from university staff and classmates, as well as levels of stress all significantly contribute to evaluation of eLearning systems success by students, whereas technical system quality, information quality, service quality, educational system quality, support system, and feature use do not. This suggests a very different scenario presented by the transition to online classes during COVID-19 than is found in literature regarding eLearning system evaluation. At the same time, socioeconomic status (SES) was found to be a statistically significant predictor for all factors contributing to eLearning evaluation, meaning the global push to online classes likely benefitted students of higher SES more than those of lower SES. This may have therefore contributed to digital divides within global higher education and have implication for future global inequality.
Keywords: 330; eLearning; Higher Education; digital inequality; COVID-19 Pandemic